Trade variety and export performance of ASEAN-5 = Kepelbagaian perdagangan dan prestasi eksport ASEAN-5 - Mat Ghani, Gairuzazmi; Sofyan, Joel Farouk (Universiti Kebangsaan Malaysia, 2014)
ASEAN-5 (Indonesia, Malaysia, Philippines, Singapore, and Thailand) exports have grown rapidly over the last few decades. This speedy growth of exports may adversely affect economic welfare if it is followed by deterioration in the terms of trade. However, increases in the variety of products traded and improvements in technology will move a country up the value chain and halt the terms of trade deterioration. Another important characteristic of ASEAN-5 exports is the heavy reliance on imported intermediate components; thus import variety may also be an important factor that affects the growth of ASEAN-5’s exports. This study measured the dynamics of the export and import varieties of ASEAN-5 for the period from 1991-2008 using variety indexes based on Shannon’s entropy. It then determined whether expansion in the varieties of products exported and imported, if any, have helped to explain the rapid growth of exports.